Confirmation or elaboration: What do yes/no declaratives want? - Seuren, L; Huiskes, M (Taylor and Francis, 2017)
Recent analyses have argued that when requests for confirmation are implemented with declarative word order, they are closure-implicative due to the relatively knowing stance indexed with the declarative. This article demonstrates, however, that in some cases participants show an orientation to both confirmation and elaboration as a relevant next action. By comparing requests for confirmation that are closure-implicative to those that are expansion-implicative, it is argued that in addition to epistemic stance, participants also orient to the lexical design features and sequential placement of these declarative yes/no-type initiating actions to determine the relevant type of response. Data are in Dutch with English translations.